Loan-To-Value Policy And Demand For Mortgage Finance: Evidence From Indonesia - Tomy Zulfikar; Nining Indroyono Soesilo (Publikasi Indonesia, 2023)
Demand for mortgage finance showed a slowdown. And also, property residential sales showed a slowdown. As is well known, most consumers buy property residential is financed by mortgage finance. Through LTV policy, the Bank of Indonesia wants to stimulate demand for mortgage finance and also property residential sales to could boost economic growth sustainably. A question is whether changes in the LTV ratio could boost economic growth sustainably and whether other factors are affecting demand for mortgage finance. This article sees the question by considering what the impacts are in both lower-middle-income and higher-middle-income provinces. By regressing the statistical model Fixed Effect Model (FEM) and Random Effect Model (REM), the result shows that LTV policy is affecting positively the demand for mortgage finance, particularly in lower-middle-income provinces. When the LTV ratio increased, the demand for mortgage finance in lower-middle-income provinces is higher than the demand for mortgage finance in higher-middle-income provinces. Moreover, mortgage finance reflects normal goods for higher-middle-income provinces while reflecting inferior goods for lower-middle-income provinces. On the other hand, higher mortgage interest lowers the demand for mortgage finance, particularly in lower-middle-income provinces.